A Case Study on Gas Venting Events in NCM523 Batteries During Thermal Runaway Under Different Pressures in a Sealed Chamber - Cheng Li; Hewu Wang; Yalun Li; Minggao Ouyang (World Electric Vehicle Journal)
The venting process is one of the most important events during the thermal runaway (TR) of lithium-ion batteries (LIBs) in determining fire accidents, while different ambient pressures will exert an influence on the venting events as well as the TR. Ternary nickel–cobalt–manganese (NCM) batteries with a 75% state of charge (SOC) were employed to conduct TR tests under different ambient pressures in a sealed chamber with dilute oxygen. It was found that elevated ambient pressure results in milder ejections in terms of jet temperature and mass loss. Gas venting characteristics were also obtained. Additionally, the amount of carbon dioxide (CO2), hydrogen (H2), methane (CH4), and ethylene (C2H4) released increase with ambient pressure, while carbon monoxide (CO) varies inversely with ambient pressure. The higher the ambient pressure is, the greater the flammability risk is. The molar amount of C, H, O, and total gases released shows a positive correlation with the maximum battery temperature and ambient pressure. This study will support the design of safety valves and help reveal the effects of venting events on the evolution of TR.